MANAGEMENT AND INNOVATION IN LATIN AMERICA: INTRODUCTION - Enrique Ogliastri (Gestão & Regionalidade, 2019)
In this introduction to the special issue of Gestão & Regionalidade entitled “Management and Innovation in Latin America,” we first review the published literature about the region, then introduce the ten new articles appearing in this issue, and finally reflect briefly on the current and future state of studies on innovation management and economics in the region. Latin America's innovation performance remains far short of its economic relevance, despite increasing academic research on the issue. Future research should highlight interactive ways to promote innovation, social innovations, public innovation, innovations for sustainability, technological innovations associated with the fourth industrial revolution, and the very specific nature of Latin American entrepreneurship.